The Rule of Law and the Pattern of Environment Protection - Mani, Muthukumara (IMF Working Papers; Working Paper ;, 2002)
We develop and test a theory of the rule of law and environmental policy formation. In our model an increase in the degree of rule of law has two opposing partial effects on environmental policy: first, a greater share of policy decisions are implemented according to law; second, industry bribery efforts increase because more is at stake. Moreover, we find that an increase in corruptibility of policymakers lowers the stringency of environmental policy. The empirical findings suggest that a greater degree of rule of law raises environmental policy stringency, but the effect is lower where corruptibility is high.